2019
DOI: 10.1123/jpah.2018-0179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Movement Programs on Motor Competence: A Systematic Review With Meta-Analysis

Abstract: Background: To use the meta-analytic approach to assess the effectiveness of different types of movement programs on motor competence (MC) in participants of all ages. Methods: Studies were retrieved by searching 13 databases and included when criteria were met. Studies were selected, and data were extracted by 2 authors. Random effects models using the standardized mean difference effect size (ES) were used to pool results. Risk of bias, heterogeneity, and inconsistency were examined. Results: Thirty-six stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…The results of the current meta-analysis, and those of previous meta-analytical studies investigating the effect of various type of interventions on motor competence, clearly suggest that structured programs are effective in influencing the development of motor competence in children and adolescents [13,14,[29][30][31]. It has been claimed, however, that interventions defined under the term "movement programs" have a better and more consistent effect on motor competence compared to physical education.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The results of the current meta-analysis, and those of previous meta-analytical studies investigating the effect of various type of interventions on motor competence, clearly suggest that structured programs are effective in influencing the development of motor competence in children and adolescents [13,14,[29][30][31]. It has been claimed, however, that interventions defined under the term "movement programs" have a better and more consistent effect on motor competence compared to physical education.…”
Section: Discussionmentioning
confidence: 56%
“…Given that the studies included in the meta-analysis originate from 13 different countries, it is difficult to assess the specific content of the physical education conducted by participants in the comparison groups. This may explain why physical education studies have reported somewhat lower effect sizes compared to other movement programs, as these latter studies typically have a waitlist, non-active, control group [31]. It should come as no surprise that active-movement-based programs introduce substantial effects above what might be general motor-development effects observed in a non-active control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These planned interventions are effective both in programs performed in the short term (4–8 weeks) and in the long term (≥6 months) [ 33 , 42 , 50 , 51 , 52 , 53 ], although shorter duration (4 weeks to 5 months) showed better results compared to longer duration (>6 months) [ 53 ] to improve the MC. In addition, the specific programs are most effective when taught by highly trained PE specialists [ 51 ], due to these interventions representing a high improvement in MC [ 54 ]. For these reasons, it is considered important to identify the type and duration of interventions so that they can help to improve MC in preschool children because there is no consensus [ 54 ].…”
Section: Introductionmentioning
confidence: 99%